Acute effects of insulin on skeletal muscle growth and differentiation genes in men with type 2 diabetes. Issue 6 (December 2019) - Dhindsa, Sandeep; Ghanim, Husam; Green, Kelly; Abuaysheh, Sanaa; Batra, Manav; Makdissi, Antoine; Chaudhuri, Ajay; Sandhu, Sartaj; Dandona, Paresh
Abstract : Aims: Insulin has anabolic effects on skeletal muscle. However, there is limited understanding of the molecular mechanisms underlying this effect in humans. We evaluated whether the skeletal muscle expression of satellite cell activator fibroblast growth factor 2 (FGF2) and muscle growth and differentiation factors are modulated acutely by insulin during euglycemic–hyperinsulinemic clamp (EHC). Design and methods: This is a secondary investigation and analysis of samples obtained from a previously completed trial investigating the effect of testosterone replacement in males with hypogonadotropic hypogonadism and type 2 diabetes. Twenty men with type 2 diabetes underwent quadriceps muscle biopsies before and after 4 h of EHC. Results: The infusion of insulin during EHC raised the expression of myogenic growth factors, myogenin (by 72 ± 20%) and myogenin differentiation protein (MyoD; by 81 ± 22%). Insulin reduced the expression of muscle hypertrophy suppressor, myogenic regulatory factor 4 (MRF4) by 34 ± 14%. In addition, there was an increase in expression of FGF receptor 2, but not FGF2, following EHC. The expression of myostatin did not change. Conclusions: Insulin has an acute potent effect on expression of genes that can stimulate muscle differentiation and growth.